2021
DOI: 10.3390/bs11030029
|View full text |Cite
|
Sign up to set email alerts
|

Associations between News Media Coverage of the 11 September Attacks and Depression in Employees of New York City Area Businesses

Abstract: Research has examined the association between contact with media coverage of mass trauma events and various psychological outcomes, including depression. Disaster-related depression research is complicated by the relatively high prevalence of the major depressive disorder in general populations even without trauma exposure. The extant research is inconclusive regarding associations between disaster media contact and depression outcomes, in part, because most studies have not distinguished diagnostic and sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Methodological rigor in these studies was demonstrated by the adherence to established criteria for trauma exposure for the diagnosis of PTSD, which is a pivotal issue for assessment of PTSD in disaster-exposed populations and necessitating differentiation of trauma from other types of stressors. A specific type of stressor examined in two studies in this review [1,4] was contact with disaster-related media, and both articles were adherent to the PTSD criteria definition of trauma exposure that specifically excludes witnessing or hearing of the disaster only through media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodological rigor in these studies was demonstrated by the adherence to established criteria for trauma exposure for the diagnosis of PTSD, which is a pivotal issue for assessment of PTSD in disaster-exposed populations and necessitating differentiation of trauma from other types of stressors. A specific type of stressor examined in two studies in this review [1,4] was contact with disaster-related media, and both articles were adherent to the PTSD criteria definition of trauma exposure that specifically excludes witnessing or hearing of the disaster only through media.…”
Section: Discussionmentioning
confidence: 99%
“…An original research article in this Special Issue by Pfefferbaum et al [4] examined MDD in relation to 9/11 news media consumption in a subset of 254 members of the same 9/11 dataset collected by the team of North and colleagues included in the two studies above. The methodological advantages of this dataset include not only structured diagnostic interviews but also the separate analysis of MDD diagnosis, symptoms, and associated levels of functioning.…”
Section: Disaster Mental Health Research In Adultsmentioning
confidence: 99%
“…Here, the term assumption is deliberately used, although institutions' inscription is an assumption and an activity. However, it is essential to note that the agency's assumption as the end of feminist political action is at the root of the need for the inscription" (Pfefferbaum et al, 2021).…”
Section: Women As Terrorists…mentioning
confidence: 99%
“…First, many studies are performed long after the initial event. For example, some are performed one to two months later [7], seven months later [6] to even 35 months later [8]. As these studies asked the respondent to recall months later how much media on a terrorist attack someone watched during the days after the attack, a recall bias is highly probable.…”
Section: Introductionmentioning
confidence: 99%